A Study on the Gap Between the Competencies of Industrial Engineering Undergraduate Students and the Competency Requirements of the Job Market in Indonesia (Asean Journal of Engineering Education, 2024)
This study examines the gap between industry expectations in Indonesia and the current competencies of undergraduate Industrial Engineering students at Universitas Sebelas Maret. The findings of this study can serve as a guideline for improving the existing Industrial Engineering program at Universitas Sebelas Maret. The research employs web scraping methods to identify appropriate indicators for assessing competency requirements in Indonesia's industrial sector. The curriculum expert team of Industrial Engineering at Universitas Sebelas Maret reviewed these indicators. Thirty-one competency performance indicators were adopted and distributed via questionnaires to 33 industry employees and 91 Industrial Engineering students from Universitas Sebelas Maret to rate the competency indicators on a scale of 1-5. We collected data and analyzed it to determine the gap between industry expectations and the current competencies of the students. The results show a significant gap between the competencies of undergraduate Industrial Engineering students at Universitas Sebelas Maret and the demands of the industry in Indonesia across all analyzed variables. The competencies with the highest gap are in the variables of Information & Communication, with a gap value of 436.8. The Information & Communication variable relates to the scope of technical skills, information system design, and programming. Conversely, we found the lowest gap in the management variable, with a gap value of 261.6. These variables are cost analysis, organizational management, marketing, and product innovation, which indicate that student competencies in this area are closer to industry expectations. This study highlights the urgent need for curriculum adjustments better to align student competencies with Indonesia's industrial sector demands.
Keywords: gap study; Indonesian industry; engineering education; industrial engineer